Assessment of Radioactivity of Some Samples of Healthy Drinking Water and Liquefied Water in Some Areas of the Capital Baghdad Using HPGE Detector System - A. Alrawi, Ammar; M. Rasheed, Essam; K. Mohammad, Kareem (Al-Nahrain Journal of Science, 2024)
In this work, a total of 20 water samples were collected from various locations inside the city of Baghdad. Each sample consists of a volume of 1 litre of water which had been obtained from multiple geographical locations. There were twelve water samples representing pure tap water sourced from various locations additionally, eight samples of mineral water were obtained from several marketplaces in Baghdad. A total of six radionuclides were detected in the water samples using the HPGe detector. These radionuclides were identified as Bi 214, Ra 226, TI 208, Bi 212, Pb 212, and K 40. Among these, Bi 214 and Ra 226 are part of the U-238 series, while TI 208, Bi 212, and Pb 212 belong to the Th 232 series. Additionally, K 40 is a naturally occurring radionuclide. The observed minimum value for the average specific activity of radionuclides in pure tap water samples was Al-Yarmouk Pure tap water. However, the sample Hay Al-qahira pure tap water exhibited the highest recorded specific activity values of radionuclides in pure tap water. The observed minimum value for the average specific activity of radionuclides in mineral water samples was Bardaa mineral water. However, the sample (W15) exhibited the highest recorded values for the specific activity of radionuclides in mineral water. The measured external dosage of natural radioactivity in water samples from Baghdad was found to be relatively low, at 0.366 mSv.y-1. This value falls below the recommended limit the United Nations Scientific Committee set on the Effects of Atomic Radiation (UNSCEAR), 1 mSv.y-1.